Clinical Utility of Salivary Biomarkers for Early Detection and Monitoring of Diabetes and Cardiovascular Disease - Ayesha Yasir, Ammar Abdullah Malik, Muhammad Azhar, Misbah Ali, Mehmood Asghar (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Diabetes mellitus and cardiovascular diseases are leading causes of morbidity and mortality worldwide. Conventional blood-based diagnostic methods, though reliable, are invasive and limit frequent monitoring. Saliva, as a non-invasive body fluid, contains biomarkers that may reflect systemic metabolic and cardiovascular changes. Objective: To evaluate the clinical utility of salivary biomarkers for early detection and monitoring of diabetes and cardiovascular disease. Methods: A cross-sectional study was conducted at Margalla Dental Hospital, Rawalpindi, in collaboration with Army Medical College, from February 2022 to March 2023. A total of 90 participants were enrolled, divided into three groups: diabetes patients, cardiovascular disease patients, and healthy controls. Unstimulated saliva samples were collected and analyzed for glucose, oxidative stress markers, inflammatory cytokines (IL-6, TNF-α, CRP), and cardiac enzymes (troponin I, CK-MB). Corresponding blood samples were also tested for correlation. Statistical analysis was performed using SPSS v26, with p < 0.05 considered significant. Results: Salivary glucose and malondialdehyde were significantly elevated in diabetes patients compared to controls, while total antioxidant capacity was reduced (p < 0.001). Inflammatory biomarkers (IL-6, TNF-α, CRP) were raised in both diabetes and cardiovascular groups, with CRP highest among cardiovascular patients. Salivary troponin I and CK-MB were significantly elevated in the cardiovascular group (p < 0.001), with mild elevations also observed in diabetics. Strong correlations were found between salivary and serum glucose (r = 0.81), CRP (r = 0.77), and troponin I (r = 0.72). Conclusion: Salivary biomarkers reliably reflect systemic alterations in diabetes and cardiovascular disease, showing strong correlations with conventional blood markers. Saliva offers a safe, simple, and non-invasive diagnostic medium that can be useful for early detection, frequent monitoring, and large-scale screening. Keywords: Saliva, biomarkers, diabetes mellitus, cardiovascular disease, non-invasive diagnostics